An All-sky 3D Dust Map Based on Gaia and LAMOST - Tao Wang; Haibo Yuan; Bingqiu Chen; Maosheng Xiang; Ruoyi Zhang; Bowen Huang; Hongrui Gu; Shuaicong Wang; Jiawei Li (The Astrophysical Journal Supplement Series)
We present a comprehensive 3D dust-reddening map covering the entire Milky Way, constructed by combining reddening estimates based on Large Sky Area Multi-Object Fiber Spectroscopy Telescope (LAMOST) low-resolution spectra ( E ( B − V ) _LAMOST ) with those derived from Gaia XP spectra ( E ( B − V ) _XP ), along with revised Gaia distances. E ( B − V ) _LAMOST values of ∼4.6 million unique sources were obtained with the standard-pair analysis using LAMOST DR11 stellar parameters and synthesized B- / V -band photometry from Gaia XP spectra, showing a typical precision of ∼0.01 mag. The E ( B − V ) _XP from the catalog of X. Zhang et al., which was derived using forward modeling of Gaia XP spectra, were cross-validated with E ( B − V ) _LAMOST , leading to the selection of ∼150 million high-reliability measurements. The combined data set achieves a median precision of ∼0.03 mag for E ( B − V ). To model the reddening–distance relationship along various lines of sight, we implemented a parametric approach that accounts for contributions from the Local Bubble, diffuse interstellar medium, and multiple potential molecular clouds. The sky was adaptively partitioned based on stellar density, resulting in angular resolutions ranging from 3 $\mathop{.}\limits{^{′} }$ 4 to 58′, with about half of the sky having a resolution better than 6 $\mathop{.}\limits{^{′} }$ 9. The reddening precision of our 3D map for individual stars reaches ∼0.01 mag in most regions at ∣ b ∣ > 20°, but degrades to 0.01–0.05 mag at ∣ b ∣ < 20°. The map reaches a maximum distance of 3–5 kpc in high-extinction regions with ∣ b ∣ < 5°, and extends to 10–15 kpc elsewhere. An interactive platform and Python package have been developed for utilization of the 3D dust map.